ANALISIS LAPORAN KEUANGAN DENGAN MENGGUNAKAN RASIO CAMELS SEBAGAI ALAT UNTUK MEMPREDIKSI KONDISI FINANCIAL DISTRESS BANK UMUM YANG TERDAFTAR DI BEI - PRIMA E S, PRATIWI (Feb Universitas Dirgantara Marsekal Suryadarma, 2016)
This research analyzed the influence of the ratio of CAMELS on the symptoms of financial distress of commercial banks listed on the Indonesia Stock Exchange between 2007 until 2009. Data that used in this research is financial statement and independent audit report from each company that published on website www.idx.co.id. Sampling method that used in this research is purposive sampling method. Analysis model that used is multiple regression analysis. The result of this research indicates that the Capital Adequacy Ratio, Assets Quality 1, Operating Expenses / Operating Income and Loan to deposit ratio does not significantly influence the financial symptoms distress. Meanwhile Good Corporate Governance and Net Interest Margin significant effect on symptoms of financial distress. Keyword: capital adequacy ratio, asset quality 1, good corporate governance, the net interest margin, operating expenses to operating income, loan to deposit ratio, financial distress condition